2006
DOI: 10.1128/aem.00454-06
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Watershed-Wide Distribution of Escherichia coli along Southern Lake Michigan: an Integrated Approach

Abstract: Recent research has highlighted the occurrence of Escherichia coli in natural habitats not directly influenced by sewage inputs. Most studies on E. coli in recreational water typically focus on discernible sources (e.g., effluent discharge and runoff) and fall short of integrating riparian, nearshore, onshore, and outfall sources. An integrated "beachshed" approach that links E. coli inputs and interactions would be helpful to understand the difference between background loading and sewage pollution; to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 32 publications
4
72
1
Order By: Relevance
“…This indicated that the presence of indigenous microflora significantly affected growth of E. coli, probably through competition and predation (2,26,28). The addition of soytone (an enzymatic digest of soybeans) or nondigested, complex, soybean meal, also enhanced the growth and survival of E. coli strain KS7-NR (Fig.…”
Section: Other Factors Influencing E Coli Growth In Soilmentioning
confidence: 92%
“…This indicated that the presence of indigenous microflora significantly affected growth of E. coli, probably through competition and predation (2,26,28). The addition of soytone (an enzymatic digest of soybeans) or nondigested, complex, soybean meal, also enhanced the growth and survival of E. coli strain KS7-NR (Fig.…”
Section: Other Factors Influencing E Coli Growth In Soilmentioning
confidence: 92%
“…Studies conducted in northern temperate regions also reveal the persistence and survival of EC through freezing winters with subsequent growth in the warmer months (Whitman & Nevers 2003;Ishii et al 2006;Whitman et al 2006 River Estuary with particle attached ENT (Fries et al 2008).…”
Section: Environmental Parameter Measurementsmentioning
confidence: 99%
“…In recent years, efforts have been directed toward an understanding of the sources and contributions of FIB and their potential interactions in the "beachshed" ecosystem, which comprises the various sources of FIB, and their influences, within the beach and its related watershed, as described by Whitman et al (356) (Fig. 1).…”
Section: Environmental Reservoirs and Extraenteric Habitatsmentioning
confidence: 99%